Student's Attachment to Social Media and the Challenges of Moderate Islamic Education (Implementation During the Covid-19 Pandemic) - Susanto, Susanto; Dwijayanto, Arik (Jurnal Ilmiah Peuradeun, 2022)
During the Covid-19 pandemic, students' dependence on gadgets and social media is stronger through online-based learning. The attachment of school-age children to gadgets and social media is prone to intersect with intolerant religious content and narratives. It is a challenge to implement moderate Islamic education in education units. This study explored the problem of school-age children's attachment to devices and analyzes the challenges of implementing moderate Islamic education in education units during the Covid-19 pandemic. This research is library research with a descriptive method. The data in this study were obtained from relevant documents regarding the research. At the same time, the primary data was a document resulting from the KPAI survey with a total sample of 14,169 respondents spread across 34 provinces in Indonesia. In contrast, secondary data were studies that were relevant to this research. This study indicated that the attachment of school-age children to gadgets and social media can be directed at strengthening moderate Islamic values through several educational contents. With intensive supervision and assistance from parents on gadgets and social media, school-age children can be controlled from content that leads to narratives of intolerance, extremism, and radicalism.